Response of hydrothermal vent vestimentiferan Riftia pachyptila to differences in habitat chemistry - Scott, Kathleen M; Boller, Amanda J; Dobrinski, Kimberly P; Le Bris, Nadine (MARINE BIOLOGY, 2012)
Vestimentiferan tubeworms, which rely on intracellular sulfide-oxidizing autotrophic bacteria for organic carbon, flourish at deep-sea hydrothermal vents despite the erratic nature of their habitat. To assess the degree to which differences in habitat chemistry (sulfide, pH/CO(2)) might impact host and symbiont metabolic activity, Riftia pachyptila tubeworms were collected from habitats with low (H(2)S {<} 0.0001 mM) and high (up to 0.7 mM) sulfide concentrations. The elemental sulfur content of the symbiont-containing trophosome organ was lower in specimens collected from the low-sulfide site. Symbiont abundance, RubisCO activity, and trophosome carbon fixation rates were not significantly different for individuals collected from low- versus high-sulfide habitats. Carbonic anhydrase activities were higher in the anterior gas exchange organs of R. pachyptila from the low-sulfide habitat. Despite large differences in habitat chemistry, symbiont abundance and autotrophic potential were consistent, while the host appears to tailor carbonic anhydrase activity to environmental CO(2) availability.
Keywords: HOV Alvin (Human Occupied Vehicle)